Understanding the trophic relationships amongst arthropods in olive grove by δN15 and δC13 stable isotope analysis. (17th February 2022) - Morente, Marina; Ruano, Francisca
Abstract: So far the limited knowledge about the diet of omnivores and generalist predators in olive groves has not allowed the clarification of their role as natural enemies. Stable isotope (δN 15 and δC 13 ) analysis is a useful tool for predicting the trophic position of a high number of species, the variety of basal resources and the flux of energy in the food web. We have explored the possible consumers of two important pests in the olive grove: adults of Prays oleae Bern (Lepidoptera: Praydidae) during its anthophagous generation and the pupae of Bactrocera oleae (Rossi) (Diptera: Tephritidae). In addition, we have included in the study the adult instar of the secondary pest Euphyllura olivina (Costa) (Hemiptera: Psyllidae). These arthropods were clustered in isotopic groups according to their similarities in δN 15 and δC 13 content assuming that, in this case, they shared similar feeding habits. Using this criterion, we obtained eight isotopically different groups of predators and eleven groups of phytophagous insects. We have used Bayesian mixing models in order to identify the potential predators of the different pests included in our study and the proportion that each pest occupied in the diet of the identified predators. Different taxa of spiders and Anthocoris nemoralis (Fabricius) (Hemiptera: Anthocoridae) have emerged as potential predators of B . oleae . Moreover, Gnaphosidae (Araneae) showed suitable isotopic characteristics to be identified as potential predator of P. oleae and A . nemoralis has been confirmed as a predator of E. olivina . The presence of E. olivina as an abundant resource encourages the settlement of natural enemies in olive orchards which feed on this secondary pest, but are also ready to feed on any insect outbreak, for example P. oleae .